2022
DOI: 10.6000/1929-4409.2020.09.148
|View full text |Cite
|
Sign up to set email alerts
|

Discretion of Power of the Indonesian National Police Impacts the Abuse of Power in the Case of Letter Forgery of Red Notice "Fugitive Djoko Tjandra"

Abstract: This research was a case study presenting a red notice that was suspected of being false against fugitive Djoko Tjandra by two police generals at the State Police of the Republic of Indonesia. This was a case study research and the research approach method was qualitative. Creswell defines the qualitative method as a research method based on a constructive perspective, that is various meanings; meanings that are constructed socially and historically to develop a theory or pattern. The researchers collected and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…The involvement of the private sector and the community in providing disaster management services is a necessity. Such conditions make it possible to view disaster management problems from a governance perspective [13], [14], [15], [16], [17], [18], [19].…”
Section: Original Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The involvement of the private sector and the community in providing disaster management services is a necessity. Such conditions make it possible to view disaster management problems from a governance perspective [13], [14], [15], [16], [17], [18], [19].…”
Section: Original Researchmentioning
confidence: 99%
“…The study results expose to the case analysis that there has been an abuse of power against the authority of the state institution. The researchers suggested that it is better if the legislators of the laws and regulations think about operational accountability that needs a law enforcement check and balance system [15].…”
Section: Conflict Theorymentioning
confidence: 99%
“…The researchers suggested that it is better if the legislators of the laws and regulations of the Police of the Republic of Indonesia think about it whether operational accountability. Therefore, there is a check and balance of law enforcement behavior carried out by the police (Riyadi, Hermanto, Harlina, & Purnomo, 2020).…”
Section: Research Originalitymentioning
confidence: 99%
“…A case study presenting a qualitative approach method expose to the case analysis that there has been an abuse of power against the authority of the state institution. It is better if the legislators of the laws and regulations think about operational accountability that need a check and balance system of the law enforcement (Riyadi, Hermanto, Harlina, & Purnomo, 2020). Capability, partnership, and information sharing do not have a significant effect on performance but must be mediated by conflict resolution in order to have a positive and significant impact.…”
Section: Publicmentioning
confidence: 99%